Polystyrene-maleic anhydride-lactide copolymer as well as preparation method and application thereof
Through a new reaction route, styrene and maleic anhydride are copolymerized and polylactic acid is condensed. Combined with terminal hydroxylation modification, a high molecular weight polystyrene-maleic anhydride-lactide copolymer was prepared, which solved the recovery of lactic acid oligomers The problems of high reuse cost and poor material performance have achieved the industrial application of high-performance polylactic acid materials.
Patent Information
- Application Number
- CN202310815624.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-05
AI Technical Summary
The existing methods for recycling and reuse of lactic acid oligomers are costly and difficult to prepare high molecular weight and high quality polylactic acid materials, and the prepared polylactic acid materials have poor heat resistance and low toughness, making them difficult to be used in industrial use.
Using a new reaction route, copolymerize styrene and maleic anhydride to prepare low molecular weight SMA, further condensate and polymerize lactic acid to obtain low molecular weight polylactic acid, and modify it through terminal hydroxylation, and then undergo high temperature polymerization with SMA to prepare high molecular weight polystyrene-maleic anhydride-lactide copolymer.
The prepared copolymer has the rigidity and strength of polylactic acid segments, the flexibility and toughness of SMA segments, excellent heat resistance and processing performance, which broadens the industrial application field, reduces production costs, and simplifies the process flow.
Smart Images

Figure CN119264358A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a technology for synthesizing high molecular weight polyester by chain extension of lactic acid oligomers, in particular to a high molecular weight polystyrene-maleic anhydride-lactide copolymer and a preparation method thereof, and belongs to the field of polymer material synthesis. Background Art
[0002] Polylactic acid is a biodegradable plastic. It uses biomass resources to ferment lactic acid, and then prepares lactide through lactic acid polycondensation and lactide polymerization to prepare polylactic acid. Its green synthesis route has incomparable advantages over traditional petroleum-based plastics. The preparation of polylactic acid materials is a hot field in the synthesis of polymer materials. Polylactic acid has the advantages of high strength and good processing performance, but the production cost of polylactic acid is relatively high. The main reason is the low yield of the product during the synthesis and preparation process. On the one hand, some lactic acid oligomers will remain in the process of preparing lactide by depolymerization of lactic acid polymers. The residual lactic acid oligomers have a large molecular weight and are difficult to recycle and depolymerize to generate lactide; on the other hand, in the distillation and purification stage of lactide, some lactic acid oligomers will be produced at the bottom of the reboiler of the distillation tower, resulting in a low yield of distillation and purification. The traditional method for recycling lactic acid oligomers is to hydrolyze lactic acid oligomers into small lactic acid molecules, which are then separated and purified and used in the preparation of lactide. However, lactide is prone to racemization during the depolymerization and distillation processes. Therefore, the lactic acid produced by the hydrolysis of lactic acid oligomers contains some dextrorotatory lactic acid, which is difficult to separate, greatly increasing the cost of recycling and reusing lactic acid oligomers.
[0003] The molecular weight of lactic acid oligomers produced during the preparation of lactide is usually from several thousand to tens of thousands. Compared with high molecular weight polylactic acid, lactic acid oligomers have low melting points and low strength, making it difficult to directly use them to prepare materials. A common method is to perform chain extension reaction on lactic acid oligomers to prepare relatively high molecular weight polylactic acid materials. However, the chain extension reaction of lactic acid oligomers is a link between macromolecules, and its reaction activity is low and the linking difficulty is high. Therefore, the molecular weight of the polylactic acid generally prepared is low, and the quality is poorer than that of polylactic acid prepared by ring-opening polymerization of lactide. Styrene-maleic anhydride copolymer (SMA) is prepared by binary copolymerization of monomers styrene (St) and maleic anhydride (MA). SMA for industrial application can be divided into two categories: one is SMA with low relative molecular weight, which can be used as a surfactant, compatibilizer, etc. for polymers, and the other is SMA with high relative molecular weight, which can be used alone as a base resin, and can also be blended and modified with a variety of polymer resins. Due to the excellent performance and outstanding molecular polarity of SMA, low molecular weight SMA resin can be used as an excellent plasticizer for polylactic acid, which can improve the toughness of polylactic acid to a certain extent. However, SMA as a plasticizer blended with polylactic acid to prepare materials does not fundamentally improve the performance of polyester materials, and the modification effect is not significant.
[0004] Chinese patent CN103254411A adds stannous octoate catalyst to lactic acid oligomers, reacts under oil bath heating conditions, rises to 175°C, and reduces pressure to 100 Pa. The reaction is stopped after 10 hours of polycondensation. In the later stage of the polycondensation reaction, the system temperature is reduced to 160°C, 0.5% of carbodiimide chain extender is added to carry out chain extension reaction, and after mechanical stirring for 2 hours, a polylactic acid product with a weight average molecular weight of 102,000 is obtained. The lactic acid oligomers are successfully synthesized into polylactic acid materials through chain extension reaction, but the molecular weight of polylactic acid is low, and the material has poor heat resistance, high brittleness, and low toughness. Chinese patent CN106344958A uses lactic acid as a raw material, dehydrates and refines it under vacuum conditions to obtain lactic acid oligomers, mixes the obtained lactic acid oligomers with a catalyst, adds them to a reaction vessel, heats them under vacuum conditions to obtain a polylactic acid intermediate, adds a chain extender HDI to the reaction vessel, heats them under vacuum conditions to obtain a polylactic acid material, although the lactic acid oligomers are prepared into polylactic acid by chain extension reaction, the shortcomings of polylactic acid being large in brittleness and low in toughness are not improved. Chinese patent CN104212085A uses SMA as a plasticizer, adds it to polystyrene, polyethylene, and polylactic acid blends, and successfully prepares a copolyester material through a twin-screw extrusion reaction. SMA as a plasticizer improves the compatibility of copolyesters to a certain extent, but the simple physical blending method does not change the thermodynamic properties of the matrix resin material itself.
[0005] In summary, the current methods for recycling and reusing lactic acid oligomers have the following main problems: (1) Although the lactic acid oligomers can be hydrolyzed into small lactic acid molecules and then prepared into polylactic acid through lactic acid, the cost of separating small lactic acid molecules is too high, which is not conducive to industrial application. (2) If lactic acid oligomers are used to prepare polylactic acid through a simple self-chain extension reaction, it is difficult to prepare high molecular weight and high quality polylactic acid materials due to the low reactivity and difficulty of linking between macromolecular chains. (3) The polylactic acid materials prepared by recycling lactic acid oligomers have poor heat resistance and low toughness, and need to be modified and processed before they can be applied industrially. Summary of the invention
[0006] In view of the above shortcomings, the present invention provides a high molecular weight polystyrene-maleic anhydride-lactide copolymer, which is prepared using lactic acid oligomers as raw materials and a reaction route different from that of the prior art. The prepared copolymer has the rigidity and strength of polylactic acid segments, the flexibility and toughness of SMA segments, excellent heat resistance and processing performance, is biodegradable, and is easy to industrialize.
[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:
[0008] The technical purpose of the first aspect of the present invention is to provide a polystyrene-maleic anhydride-lactide copolymer having a structure of general formula I:
[0009]
[0010] Wherein, R1 and R2 are independently selected from C1-C10 substituted or unsubstituted alkyl, C6-C30 substituted or unsubstituted alicyclic group or aryl group; preferably C2-C6 substituted or unsubstituted alkyl, C6-C15 alicyclic group or aryl group;
[0011] x is an integer of 5-50, preferably an integer of 15-25; y is an integer of 5-50, preferably an integer of 15-25; n is an integer of 10-120, preferably an integer of 40-100, and p is an integer of 20-260, preferably an integer of 60-120.
[0012] Further, as a more specific embodiment, R1 is selected from -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2CH2-,
[0013] One of the groups.
[0014] Further, as a more specific embodiment, R2 is selected from -CH2CH2-, -CH2CH2CH2-, -CH(CH3)CH2-, CH2CH2CH2CH2- and One of the groups.
[0015] Furthermore, the weight average molecular weight of the polystyrene-maleic anhydride-lactide copolymer is 1.0×10 5 -3.5×10 5 , preferably 2.0×10 5 -3.0×10 5 .
[0016] Furthermore, the right-angle tear strength of the polystyrene-maleic anhydride-lactide copolymer is not less than 90 kN / m, preferably 100-120 kN / m; and the elongation at break is not less than 75%, preferably 80-105%.
[0017] Furthermore, the glass transition temperature of the polystyrene-maleic anhydride-lactide copolymer is 120-150°C.
[0018] In the present invention, the right-angle tear strength and elongation at break are measured by a universal mechanical tester; the weight average molecular weight is measured by a gel chromatography method; and the glass transition temperature is measured by a differential scanning calorimeter method; which are described in detail below.
[0019] The technical purpose of the second aspect of the present invention is to provide a method for preparing a polystyrene-maleic anhydride-lactide copolymer, comprising the following contents:
[0020] (1) polymerizing maleic anhydride and styrene to obtain a low molecular weight SMA polymer;
[0021] (2) prepolymerizing lactic acid or lactic acid oligomers at low temperature in the presence of a catalyst to obtain low molecular weight polylactic acid, and adding a diol to terminally hydroxylate the low molecular weight polylactic acid to obtain terminally hydroxylated low molecular weight polylactic acid;
[0022] (3) heating and melting the end-hydroxylated low molecular weight polylactic acid obtained in step (2), adding the low molecular weight SMA polymer obtained in step (1) into the melt, continuously adding diisocyanate dropwise during the reaction, and polymerizing at high temperature to prepare the polystyrene-maleic anhydride-lactide copolymer.
[0023] Furthermore, in step (1), the maleic anhydride and styrene are polymerized in the presence of an initiator, and the initiator is selected from at least one of dicumyl peroxide and azobisisobutyronitrile, preferably dicumyl peroxide.
[0024] Furthermore, the specific process of step (1) is: dissolving maleic anhydride in an organic solvent, adding an initiator and heating at a constant temperature, adding styrene monomer dropwise to the reaction solution, continuing the heating reaction, adding a precipitant after the reaction is completed, filtering and drying to obtain a low molecular weight SMA polymer; wherein the organic solvent is selected from at least one of butyl acetate, n-heptane and acetone, preferably acetone; and the precipitant is selected from at least one of ether, anhydrous methanol and anhydrous ethanol, preferably anhydrous ethanol.
[0025] Furthermore, in step (1), the amount of the initiator added is 0.1-5%, preferably 0.5-2.0%, of the maleic anhydride, and the amount of styrene added is 100-300%, preferably 150-250%, of the maleic anhydride, by weight.
[0026] Furthermore, step (1) is carried out in an inert atmosphere, preferably under the protection of a nitrogen flow, with a constant temperature reaction of 50-150°C, preferably 80-120°C; a reaction time of 1-8h, preferably 2-6h; and a flow rate of the inert atmosphere protective gas of 0.5-6m / s, preferably 2-4m / s.
[0027] The main reaction occurring in step (1) is shown below:
[0028]
[0029] Furthermore, the molecular weight of the low molecular weight SMA polymer in step (1) is 1000-10000, preferably 3000-5000.
[0030] Furthermore, the lactic acid oligomer in step (2) is preferably a lactide depolymerization substrate or a distillation substrate, preferably a lactide distillation substrate, the catalyst is selected from one or more of stannous octoate, zinc lactate, trialkylaluminum, triisobutylaluminum and stannous chloride, preferably stannous octoate; the diol is selected from one or more of ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, bisphenol A or 1,4-butanediol, preferably 1,4-butanediol.
[0031] Furthermore, in step (2), the amount of catalyst added is 0.01-1% by weight of lactic acid or lactic acid oligomers, preferably 0.05-0.5%; the amount of diol added is 0.01-0.1% by weight of lactic acid or lactic acid oligomers, preferably 0.02-0.08%.
[0032] Furthermore, step (2) is a low-temperature polymerization under the protection of an inert atmosphere, preferably a nitrogen flow, the polymerization reaction temperature is 100-150°C, preferably 120-140°C; the reaction pressure is 100-1000kPa, preferably 200-500kPa; the flow rate of the inert atmosphere protective gas is 0.5-6m / s, preferably 2-4m / s; the polymerization reaction time is 2-15h, preferably 3-8h, and the reaction time of the end hydroxylation is 1-8h, preferably 2-6h.
[0033] In the present invention, unless otherwise specified, the pressures mentioned refer to absolute pressures.
[0034] Furthermore, the molecular weight of the terminal hydroxylated low molecular weight polylactic acid obtained in step (2) is 2000-20000, preferably 5000-10000.
[0035] Furthermore, the diisocyanate in step (3) is one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI) or hexamethylene diisocyanate (HDI), preferably hexamethylene diisocyanate (HDI), and the amount of diisocyanate added is 0.01-0.1% by weight, preferably 0.02-0.08% by weight of the terminal hydroxylated low molecular weight polylactic acid, and the amount of SMA added is 20-80% by weight, preferably 30-60% by weight of the terminal hydroxylated low molecular weight polylactic acid.
[0036] The main reaction process of step (3) is shown in the following formula:
[0037]
[0038] Furthermore, step (3) is polymerized under the protection of an inert atmosphere, preferably a nitrogen flow, the polymerization reaction temperature is 100-200°C, preferably 120-180°C; the reaction pressure is 100-1000kPa, preferably 200-500kPa; the flow rate of the inert atmosphere protective gas is 0.5-6m / s, preferably 2-4m / s; the polymerization reaction time is 4-20h, preferably 6-18h.
[0039] The technical purpose of the third aspect of the present invention is to provide an application of a polystyrene-maleic anhydride-lactide copolymer, wherein the polystyrene-maleic anhydride-lactide copolymer is applied to the fields of automotive interior, coatings, textiles, printing and dyeing, and medical supplies.
[0040] Compared with the existing technology, the present invention has the following advantages:
[0041] (1) Compared with the prior art, the present invention provides a new route for synthesizing polystyrene-maleic anhydride-lactide copolymers, firstly, styrene and maleic anhydride are copolymerized to prepare low molecular weight polystyrene-maleic anhydride (SMA), then lactic acid or lactic acid oligomers are further condensed to synthesize low molecular weight polylactic acid, the obtained low molecular weight polylactic acid is terminally hydroxylated, and finally, under the action of a chain extender, the terminally hydroxylated low molecular weight polylactic acid and SMA are subjected to high temperature polymerization to prepare polystyrene-maleic anhydride-lactide copolymers.
[0042] (2) Since polystyrene-maleic anhydride-lactide copolymer has both the rigidity and strength of polylactic acid segments and the flexibility and toughness of SMA segments, it has excellent mechanical properties, heat resistance and processing properties, which broadens the field of industrial application.
[0043] (3) The copolymerization process of SMA and end-hydroxylated low molecular weight polylactic acid does not produce small molecules, the polymerization speed is fast, the time is short, and it is easy to industrialize.
[0044] (4) In the present invention, lactic acid oligomers can be directly used as raw materials, eliminating the process of hydrolyzing and recycling lactic acid oligomers. Lactic acid oligomers can be directly used to prepare copolyester materials, providing a new use for lactic acid oligomers produced in the depolymerization and distillation stages of lactide, thereby greatly reducing production costs.
[0045] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 It is the Fourier infrared spectra of pure PLA (polylactic acid) and polystyrene-maleic anhydride-lactide copolyester (PLSMA) prepared in Example 1. DETAILED DESCRIPTION
[0047] The following non-limiting examples can enable those of ordinary skill in the art to more fully understand the present invention, but do not limit the present invention in any way. The reagents, materials, and instruments involved in the following examples, unless otherwise specified, can all be obtained through regular commercial channels. The tests and inspection methods involved in the following examples, unless otherwise specified, are all existing tests and inspection methods in the prior art. The following examples provide a clear and complete description of the technical scheme of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. All obvious changes or changes derived from the present invention still fall within the scope of protection of the present invention.
[0048] The following are the test methods for the performance parameters involved in the embodiments:
[0049] (1) Right-angle tear strength and elongation at break: measured using a universal mechanical testing machine in accordance with GB / T1039-1992.
[0050] (2) Glass transition temperature: measured by differential scanning calorimetry (DSC) (DSC 204, NETZSCH, Germany). Test conditions: sample weight 5-10 mg, firstly, the sample was heated from room temperature to 200°C at a heating rate of 10°C / min, and kept isothermally for 5 min to eliminate the thermal history of the sample; then, the sample was quickly cooled to -20°C, and then heated from -20°C to 200°C at a heating rate of 10°C / min; nitrogen was introduced as protective gas during the entire test, and the flow rate of nitrogen was set to 50 mL / min.
[0051] (3) Polymer weight average molecular weight: measured by gel permeation chromatography (GPC Waters 1515 system) using a gel permeation chromatography (GPC Waters 1515 system) to characterize the molecular weight of the polylactic acid graft copolymer sample. Chromatographically pure THF was used as the mobile phase, the flow rate was 1.0 ml / min, and the column temperature was 35°C. Before the test, the sample was dissolved in THF at a concentration of 5 mg / mL, filtered through a polytetrafluoroethylene (PTFE) filter membrane with a pore size of 0.22 μm, and then injected, and calibrated with a narrow distribution polystyrene (PS) standard.
[0052] Example 1
[0053] (1) Maleic anhydride and acetone solvent are added to a reactor, and an initiator diisopropylbenzene peroxide is added. At the same time, styrene monomer is added dropwise to the reactor, and the reaction is carried out at a constant temperature under a nitrogen flow condition. After the reaction is completed, anhydrous ethanol precipitant is added, and the reaction is filtered and dried to obtain a low molecular weight SMA polymer. The constant temperature reaction temperature is 80°C, the reaction time is 3 hours, and the gas flow rate of the nitrogen flow protection is 3 m / s; based on the weight of maleic anhydride, the amount of initiator diisopropylbenzene peroxide added is 2% of the maleic anhydride, and the amount of styrene added is 180% of the maleic anhydride.
[0054] (2) Lactic acid oligomers are mixed with stannous octoate, and low-temperature prepolymerization is performed under nitrogen flow and negative pressure to obtain low molecular weight polylactic acid, and 1,4-butanediol is added to terminally hydroxylate the low molecular weight polylactic acid to obtain terminally hydroxylated low molecular weight polylactic acid. The polymerization temperature is 120°C, and the reaction pressure is 300 kPa; the gas flow rate of the nitrogen flow is 3 m / s, the polymerization time is 4 hours, and the terminal hydroxylation reaction time is 3 hours; based on the weight of the lactic acid oligomer, the amount of stannous octoate added is 0.1% of the lactic acid oligomer; the amount of 1,4-butanediol added is 0.03% of the lactic acid oligomer.
[0055] (3) The end-hydroxylated low molecular weight polylactic acid obtained in step (2) is heated and melted, and the low molecular weight SMA polymer obtained in step (1) is added to the melt. Hexamethylene diisocyanate is continuously added dropwise during the reaction, and high-temperature polymerization is performed under nitrogen flow and negative pressure conditions to prepare polystyrene-maleic anhydride-lactide copolyester (PLSMA). The polymerization temperature is 150° C.; the reaction pressure is 300 kPa; the gas flow rate of the nitrogen flow is 3 m / s; the polymerization time is 8 h; based on the weight of the end-hydroxylated low molecular weight polylactic acid, the amount of hexamethylene diisocyanate added is 0.03% of the end-hydroxylated low molecular weight polylactic acid, and the amount of SMA added is 40% of the end-hydroxylated low molecular weight polylactic acid.
[0056] Performance characterization: The right-angle tear strength of the polystyrene-maleic anhydride-lactide copolymer material was measured to be 100KN / m, the elongation at break was 80%, the glass transition temperature was 125°C, the weight average molecular weight of the end-hydroxylated low molecular weight polylactic acid was 5500, the weight average molecular weight of the low molecular weight SMA was 3200, and the weight average molecular weight of the polystyrene-maleic anhydride-lactide copolyester was 1.91×10 5 .
[0057] Figure 1 The Fourier transform infrared spectra of pure PLA (polylactic acid) and polystyrene-maleic anhydride-lactide copolyester (PLSMA) prepared in Example 1 are shown in the accompanying Figure 1 It can be seen that in the infrared spectrum curve of pure PLA, 1750cm -1 1186cm-1 The strong characteristic absorption peaks of C=O group and the stretching vibration peak of CO are shown in the infrared spectrum curve of PLSMA, which is 1380cm -1 1020cm -1 The characteristic absorption peak of CN and the stretching vibration peak of CH on the benzene ring appeared at , indicating that the SMA copolymer segment was introduced into the PLA macromolecular chain segment.
[0058] Example 2
[0059] (1) Maleic anhydride and acetone solvent are added to a reactor, and an initiator diisopropylbenzene peroxide is added. At the same time, styrene monomer is added dropwise to the reactor, and the reaction is carried out at a constant temperature under a nitrogen flow condition. After the reaction is completed, anhydrous ethanol precipitant is added, and the reaction is filtered and dried to obtain a low molecular weight SMA polymer. The constant temperature reaction temperature is 90° C., the reaction time is 4 hours, and the gas flow rate of the nitrogen flow protection is 3 m / s; based on the weight of maleic anhydride, the amount of initiator diisopropylbenzene peroxide added is 1.5% of the maleic anhydride, and the amount of styrene added is 200% of the maleic anhydride.
[0060] (2) Lactic acid oligomers are mixed with stannous octoate, and low-temperature prepolymerization is performed under nitrogen flow and negative pressure to obtain low molecular weight polylactic acid, and 1,4-butanediol is added to terminally hydroxylate the low molecular weight polylactic acid to obtain terminally hydroxylated low molecular weight polylactic acid. The polymerization temperature is 125°C, and the reaction pressure is 300 kPa; the gas flow rate of the nitrogen flow is 3 m / s, the polymerization time is 5 h, and the terminal hydroxylation time is 4 h; based on the weight of the lactic acid oligomer, the amount of stannous octoate added is 0.2% of the lactic acid oligomer; the amount of 1,4-butanediol added is 0.04% of the lactic acid oligomer.
[0061] (3) The end-hydroxylated low molecular weight polylactic acid obtained in step (2) is heated and melted, and the low molecular weight SMA polymer obtained in step (1) is added to the melt. Hexamethylene diisocyanate is continuously added dropwise during the reaction, and high-temperature polymerization is carried out under nitrogen flow and negative pressure conditions to prepare polystyrene-maleic anhydride-lactide copolyester (PLSMA). The polymerization temperature is 160° C.; the reaction pressure is 300 kPa; the gas flow rate of the nitrogen flow is 3 m / s; the polymerization time is 10 h; based on the weight of the end-hydroxylated low molecular weight polylactic acid, the amount of hexamethylene diisocyanate added is 0.04% of the end-hydroxylated low molecular weight polylactic acid, and the amount of SMA added is 45% of the end-hydroxylated low molecular weight polylactic acid.
[0062] Performance characterization: The right-angle tear strength of the polystyrene-maleic anhydride-lactide copolyester material was measured to be 108KN / m, the elongation at break was 85%, the glass transition temperature was 132°C, the weight average molecular weight of the end-hydroxylated low molecular weight polylactic acid was 6200, the weight average molecular weight of the low molecular weight SMA was 3600, and the weight average molecular weight of the polystyrene-maleic anhydride-lactide copolyester was 2.16×10 5 .
[0063] Example 3
[0064] (1) Maleic anhydride and acetone solvent are added to a reactor, and an initiator diisopropylbenzene peroxide is added. At the same time, styrene monomer is added dropwise to the reactor, and the reaction is carried out at a constant temperature under a nitrogen flow condition. After the reaction is completed, anhydrous ethanol precipitant is added, and the reaction is filtered and dried to obtain a low molecular weight SMA polymer. The constant temperature reaction temperature is 100° C., the reaction time is 5 hours, and the gas flow rate of the nitrogen flow protection is 3 m / s; based on the weight of maleic anhydride, the amount of initiator diisopropylbenzene peroxide added is 1.5% of the maleic anhydride, and the amount of styrene added is 220% of the maleic anhydride.
[0065] (2) Lactic acid oligomers are mixed with stannous octoate, and low-temperature prepolymerization is performed under nitrogen flow and negative pressure to obtain low molecular weight polylactic acid, and 1,4-butanediol is added to terminally hydroxylate the low molecular weight polylactic acid to obtain terminally hydroxylated low molecular weight polylactic acid. The polymerization temperature is 130° C. and the reaction pressure is 300 kPa; the gas flow rate of the nitrogen flow is 3 m / s, the polymerization time is 6 h, and the terminal hydroxylation time is 4 h; based on the weight of the lactic acid oligomer, the amount of stannous octoate added is 0.3% of the lactic acid oligomer; the amount of 1,4-butanediol added is 0.04% of the lactic acid oligomer.
[0066] (3) The end-hydroxylated low molecular weight polylactic acid obtained in step (2) is heated and melted, and the low molecular weight SMA polymer obtained in step (1) is added to the melt, and hexamethylene diisocyanate is continuously added dropwise during the reaction, and high-temperature polymerization is carried out under nitrogen flow and negative pressure conditions to prepare polystyrene-maleic anhydride-lactide copolyester (PLSMA). The polymerization temperature is 165° C.; the reaction pressure is 300 kPa; the gas flow rate of the nitrogen flow is 3 m / s; the polymerization time is 12 h; based on the weight of the end-hydroxylated low molecular weight polylactic acid, the amount of hexamethylene diisocyanate added is 0.05% of the end-hydroxylated low molecular weight polylactic acid, and the amount of SMA added is 50% of the end-hydroxylated low molecular weight polylactic acid.
[0067] Performance characterization: The right-angle tear strength of the polystyrene-maleic anhydride-lactide copolyester material was measured to be 116KN / m, the elongation at break was 91%, the glass transition temperature was 138°C, the weight average molecular weight of the end-hydroxylated low molecular weight polylactic acid was 7100, the weight average molecular weight of the low molecular weight SMA was 4000, and the weight average molecular weight of the polystyrene-maleic anhydride-lactide copolyester was 2.33×10 5 .
[0068] Example 4
[0069] (1) Add maleic anhydride and acetone solvent to a reactor, add initiator diisopropylbenzene peroxide, and simultaneously drop styrene monomer into the reactor, react at a constant temperature under nitrogen flow conditions, add anhydrous ethanol precipitant after the reaction, filter and dry to obtain a low molecular weight SMA polymer. The constant temperature reaction temperature is 110°C, the reaction time is 6 hours, and the gas flow rate of the nitrogen flow protection is 3 m / s; based on the weight of maleic anhydride, the amount of initiator diisopropylbenzene peroxide added is 2% of maleic anhydride, and the amount of styrene added is 250% of maleic anhydride.
[0070] (2) Lactic acid oligomers are mixed with stannous octoate, and low-temperature prepolymerization is performed under nitrogen flow and negative pressure to obtain low molecular weight polylactic acid, and 1,4-butanediol is added to terminally hydroxylate the low molecular weight polylactic acid to obtain terminally hydroxylated low molecular weight polylactic acid. The polymerization temperature is 140°C, and the reaction pressure is 300 kPa; the gas flow rate of the nitrogen flow is 3 m / s, the polymerization time is 8 hours, and the terminal hydroxylation reaction time is 5 hours; based on the weight of the lactic acid oligomer, the amount of stannous octoate added is 0.4% of the lactic acid oligomer; the amount of 1,4-butanediol added is 0.06% of the lactic acid oligomer.
[0071] (3) The end-hydroxylated low molecular weight polylactic acid obtained in step (2) is heated and melted, and the low molecular weight SMA polymer obtained in step (1) is added to the melt. Hexamethylene diisocyanate is continuously added dropwise during the reaction, and high-temperature polymerization is carried out under nitrogen flow and negative pressure conditions to prepare polystyrene-maleic anhydride-lactide copolyester (PLSMA). The polymerization temperature is 165° C.; the reaction pressure is 300 kPa; the gas flow rate of the nitrogen flow is 3 m / s; the polymerization time is 12 h; based on the weight of the end-hydroxylated low molecular weight polylactic acid, the amount of hexamethylene diisocyanate added is 0.06% of the end-hydroxylated low molecular weight polylactic acid, and the amount of SMA added is 55% of the end-hydroxylated low molecular weight polylactic acid.
[0072] Performance characterization: The right-angle tear strength of the polystyrene-maleic anhydride-lactide copolyester material was measured to be 120KN / m, the elongation at break was 101%, the glass transition temperature was 145°C, the weight average molecular weight of the end-hydroxylated low molecular weight polylactic acid was 8000, the weight average molecular weight of the low molecular weight SMA was 5200, and the weight average molecular weight of the polystyrene-maleic anhydride-lactide copolyester was 2.51×10 5 .
[0073] Example 5
[0074] (1) Add maleic anhydride and acetone solvent to a reactor, add initiator diisopropylbenzene peroxide, and simultaneously drop styrene monomer into the reactor, react at a constant temperature under nitrogen flow conditions, add anhydrous ethanol precipitant after the reaction, filter and dry to obtain a low molecular weight SMA polymer. The constant temperature reaction temperature is 120°C, the reaction time is 6 hours, and the gas flow rate of the nitrogen flow protection is 3 m / s; based on the weight of maleic anhydride, the amount of initiator diisopropylbenzene peroxide added is 2% of maleic anhydride, and the amount of styrene added is 250% of maleic anhydride.
[0075] (2) Lactic acid oligomers are mixed with stannous octoate, and low-temperature prepolymerization is performed under nitrogen flow and negative pressure to obtain low molecular weight polylactic acid, and 1,4-butanediol is added to terminally hydroxylate the low molecular weight polylactic acid to obtain terminally hydroxylated low molecular weight polylactic acid. The polymerization temperature is 140°C, and the reaction pressure is 300 kPa; the gas flow rate of the nitrogen flow is 3 m / s, the polymerization time is 8 hours, and the terminal hydroxylation reaction time is 6 hours; based on the weight of the lactic acid oligomer, the amount of stannous octoate added is 0.5% of the lactic acid oligomer; the amount of 1,4-butanediol added is 0.08% of the lactic acid oligomer.
[0076] (3) The end-hydroxylated low molecular weight polylactic acid obtained in step (2) is heated and melted, and the low molecular weight SMA polymer obtained in step (1) is added to the melt, and hexamethylene diisocyanate is continuously added dropwise during the reaction, and high-temperature polymerization is carried out under nitrogen flow and negative pressure conditions to prepare polystyrene-maleic anhydride-lactide copolyester (PLSMA). The polymerization temperature is 170°C; the reaction pressure is 300kPa; the gas flow rate of the nitrogen flow is 3m / s; the polymerization time is 16h; based on the weight of the end-hydroxylated low molecular weight polylactic acid, the amount of hexamethylene diisocyanate added is 0.08% of the end-hydroxylated low molecular weight polylactic acid, and the amount of SMA added is 60% of the end-hydroxylated low molecular weight polylactic acid.
[0077] Performance characterization: The right-angle tear strength of the polystyrene-maleic anhydride-lactide copolyester material was measured to be 105KN / m, the elongation at break was 83%, the glass transition temperature was 128°C, the weight average molecular weight of the end-hydroxylated low molecular weight polylactic acid was 10600, the weight average molecular weight of the low molecular weight SMA was 8100, and the weight average molecular weight of the polystyrene-maleic anhydride-lactide copolyester was 2.05×10 5 .
Claims
1. A polystyrene-maleic anhydride-lactide copolymer, characterized in that: It has the structure of general formula I: Wherein, R1 and R2 are independently selected from C1-C10 substituted or unsubstituted alkyl, C6-C30 substituted or unsubstituted alicyclic group or aryl group; preferably C2-C6 substituted or unsubstituted alkyl, C6-C15 alicyclic group or aryl group; x is an integer of 5-50, preferably an integer of 15-25; y is an integer of 5-50, preferably an integer of 15-25; n is an integer of 10-120, preferably an integer of 40-100, and p is an integer of 20-260, preferably an integer of 60-120.
2. The polystyrene-maleic anhydride-lactide copolymer according to claim 1, characterized in that: R1 is selected from -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2CH2-, One of the groups.
3. The polystyrene-maleic anhydride-lactide copolymer according to claim 1, characterized in that: R2 is selected from -CH2CH2-, -CH2CH2CH2-, -CH(CH3)CH2-, CH2CH2CH2CH2- and One of the groups.
4. The polystyrene-maleic anhydride-lactide copolymer according to claim 1, characterized in that: Its weight average molecular weight is 1.0×10 5 -3.5×10 5 , preferably 2.0×10 5 -3.0×10 5 .
5. The polystyrene-maleic anhydride-lactide copolymer according to claim 1, characterized in that: The right-angle tearing strength is not less than 90 kN / m, preferably 100-120 kN / m; the elongation at break is not less than 75%, preferably 80-105%.
6. The polystyrene-maleic anhydride-lactide copolymer according to claim 1, characterized in that: Its glass transition temperature is 120-150°C.
7. The method for preparing the polystyrene-maleic anhydride-lactide copolymer according to claim 1, comprising the following contents: (1) polymerizing maleic anhydride and styrene to obtain a low molecular weight SMA polymer; (2) prepolymerizing lactic acid or lactic acid oligomers at low temperature in the presence of a catalyst to obtain low molecular weight polylactic acid, and adding a diol to terminally hydroxylate the low molecular weight polylactic acid to obtain terminally hydroxylated low molecular weight polylactic acid; (3) heating and melting the end-hydroxylated low molecular weight polylactic acid obtained in step (2), adding the low molecular weight SMA polymer obtained in step (1) into the melt, continuously adding diisocyanate dropwise during the reaction, and polymerizing at high temperature to prepare the polystyrene-maleic anhydride-lactide copolymer.
8. The preparation method according to claim 7, characterized in that: In step (1), maleic anhydride and styrene are polymerized in the presence of an initiator, wherein the initiator is selected from at least one of dicumyl peroxide and azobisisobutyronitrile, and the amount of the initiator added is 0.1-5% by weight of the maleic anhydride, and the amount of styrene added is 100-300% by weight of the maleic anhydride.
9. The preparation method according to claim 7, characterized in that: The molecular weight of the SMA polymer obtained in step (1) is 1000-10000.
10. The preparation method according to claim 7, characterized in that: The specific process of step (1) is: dissolving maleic anhydride in an organic solvent, adding an initiator and heating at a constant temperature, dropping styrene monomer into the reaction solution, continuing heating reaction, adding a precipitant after the reaction is completed, filtering and drying to obtain a low molecular weight SMA polymer; wherein the organic solvent is selected from at least one of butyl acetate, n-heptane and acetone, and the precipitant is selected from at least one of ether, anhydrous methanol and anhydrous ethanol.
11. The preparation method according to claim 7, characterized in that: Step (1) is a constant temperature reaction under the protection of an inert atmosphere, the reaction temperature is 50-150° C., and the reaction time is 1-8 hours.
12. The preparation method according to claim 7, characterized in that: The catalyst in step (2) is selected from one or more of stannous octoate, zinc lactate, trialkylaluminum, triisobutylaluminum and stannous chloride, and the amount of the catalyst added is 0.01-1% by weight of the lactic acid or lactic acid oligomer.
13. The preparation method according to claim 7, characterized in that: The diol in step (2) is selected from one or more of ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, bisphenol A or 1,4-butanediol. The amount of diol added is 0.01-0.1% by weight of lactic acid or lactic acid oligomer.
14. The preparation method according to claim 7, characterized in that: Step (2) is low-temperature polymerization under the protection of an inert atmosphere, the polymerization reaction temperature is 100-150° C., the reaction pressure is 100-1000 kPa, and the polymerization reaction time is 2-15 hours.
15. The preparation method according to claim 7, characterized in that: The reaction time of the terminal hydroxylation in step (2) is 1-8 hours, and the molecular weight of the terminal hydroxylated low molecular weight polylactic acid obtained in step (2) is 2000-20000.
16. The preparation method according to claim 7, characterized in that: The diisocyanate in step (3) is one or more of toluene diisocyanate, diphenylmethane diisocyanate or hexamethylene diisocyanate, and the amount of diisocyanate added is 0.01-0.1% by weight of the terminal hydroxylated low molecular weight polylactic acid.
17. The preparation method according to claim 7, characterized in that: In step (3), the amount of SMA added is 20-80% of the terminal hydroxylated low molecular weight polylactic acid.
18. The preparation method according to claim 7, characterized in that: Step (3) is polymerization under the protection of an inert atmosphere, the polymerization reaction temperature is 100-200° C., the reaction pressure is 100-1000 kPa, and the polymerization reaction time is 4-20 h.
19. Use of the polystyrene-maleic anhydride-lactide copolymer according to claim 1, wherein the polystyrene-maleic anhydride-lactide copolymer is used in the fields of automobile interior, coatings, textiles, printing and dyeing, and medical products.
Citation Information
Patent Citations
Method for preparing polylactic acid-based high-elasticity copolymer
CN101899139A
Polylactic acid material composition, polylactic acid material and its preparation method
CN102719063A
Lactide copolymer, method for producing same, and resin composition comprising same
CN104837889A
Technology for preparing high-molecular-weight MPLGA by directly grafting maleic anhydride onto PLGA
CN105315412A
Multi-block aliphatic-aromatic-polylactic acid copolyester, and preparation method thereof
CN107973907A